2016
DOI: 10.1785/0220150263
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Fracturing and Seismicity in the Western Canada Sedimentary Basin

Abstract: The development of most unconventional oil and gas resources relies upon subsurface injection of very large volumes of fluids, which can induce earthquakes by activating slip on a nearby fault. During the last 5 years, accelerated oilfield fluid injection has led to a sharp increase in the rate of earthquakes in some parts of North America. In the central United States, most induced seismicity is linked to deep disposal of coproduced wastewater from oil and gas extraction. In contrast, in western Canada most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
302
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 373 publications
(312 citation statements)
references
References 46 publications
9
302
0
1
Order By: Relevance
“…[26][27][28][29] Engineering monitoring in this study proved this point, the maximal moment magnitude Some scholars pointed out that West Canadian reservoirs and Sichuan Basin in China experienced anomalous activity during multistage fracturing, the microseismic moment magnitude was more than 4.…”
Section: Slippingsupporting
confidence: 67%
“…[26][27][28][29] Engineering monitoring in this study proved this point, the maximal moment magnitude Some scholars pointed out that West Canadian reservoirs and Sichuan Basin in China experienced anomalous activity during multistage fracturing, the microseismic moment magnitude was more than 4.…”
Section: Slippingsupporting
confidence: 67%
“…In Canada, development of shale gas and shale oil resources is focused within the WCSB, where seismic activity has been increasing since 2010 . Most observed events in the WCSB with M ≥ 3 have been associated with oil and gas activity since 1985, and Atkinson et al (2016) determined that from 2010 to 2015 more than half of all M ≥ 3 events correlated spatially and temporally with hydraulic fracturing operations. It was determined that only ~0.3% of all hydraulic fracturing operations are associated with M ≥ 3 events, but as the number of these operations grows in Alberta and eastern British Columbia, the cumulative risk of inducing earthquakes becomes greater .…”
Section: Seismicity Ratesmentioning
confidence: 99%
“…In the United States, where the industry is well established, a marked increase in felt seismicity (M > 3) occurred [3]. Previously it was argued that this was due to injection to depths of several kilometres [12], but recent work in Canada [13] has shown that processes at shallower depths (i.e., hydraulic fracturing of the reservoir) may also lead to felt seismicity.…”
Section: Introductionmentioning
confidence: 99%